The Impact of The Role of Parents in Increasing Motivation for Achievement of Fencing Athletes - Agnes Suharniati Sihombing; Sri Widaningsih; Henry Asmara (STKIP Pasundan Press, 2025)
Parents play an important role in increasing the motivation of fencing athletes to excel, but they often lack a understanding of how to support children effectively. The purpose of the researcher was to see if there was an influence on the role of parents and how much of an impact the role of parents to increase children's motivation for achievement in the fence club. This study uses a quantitative associative research design with a simple linear regression approach, with a data collection technique, namely a questionnaire. The results of the study showed that there was an influence of the role of parents on the motivation of fencing athletes' achievements, with a percentage result of 62.4%. To increase athlete motivation, parents need to change their focus to not only supervising, but also inspiring and always meeting their children's training needs.